Preparation and characterization of monetites co-doped with Ni/Al, Ni/Mn and Al/Mn - Kaygili, Omer; Tatar, Cengiz; Keser, Serhat; Bulut, Niyazi (Elsevier Science Bv, 2017)
Ni/Al, Ni/Mn and Al/Mn co-doped monetite samples, as well as the undoped monetite, were prepared via wet chemical method. The structural characterization of the as-synthesized samples was done using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy techniques. It is seen that all the samples are well-crystallized, except for Al/Mn co-doped monetite, and their phase compositions and crystal structures are affected significantly by kind of the as-mentioned co-dopants. Plate-like morphology, which is independent of the compositions of the samples, is observed for each sample. It is seen that all the as-investigated parameters can be controlled by kind of the co-additives. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Bioceramics; Crystal structure; X-ray techniques